Peran Media Komunikasi Digital Pada Pola Komunikasi Guru dan Murid - Rahajeng Puspito Sari (Avant Garde, 2021)
Communication patterns between teachers and students were previously limited to classrooms. Harmony of communication between teachers and students is something that must be considered in order for learning activities to be more maximal and the objectives of learning can be achieved. The dissemination of learning information during this time often encounters obstacles due to limited communication space. The limitations of communication space make the dissemination of information ineffective and often miss communication. However, nowadays many communication technologies are designed to facilitate the dissemination of information. One of the technology products that people are interested in is the internet. Social media in this digital age can be easily accessed by the public through their smartphones by downloading the mobile application anytime and anywhere. But it turns out that there is a change in communication patterns between teachers and students with the use of digital media. The distance and pattern of formal communication becomes changed with the existence of this digital media. The distance and pattern of formal communication becomes changed with the existence of this digital media. This study uses theories and concepts related to digital media, communication patterns of teachers and students using qualitative methods. The research approach uses qualitative descriptive. The object of this study is the pattern of communication between teachers and students at SMK PGRI Prohibition in using digital communication media. The objectives of this are explained, namely: (1) Found and identified the role of digital media in communication patterns between teachers and students (2) Obtained forms of courtesy deviations due to communication using digital media (3) obtained communication patterns between teachers and students in conversations through WhatsApp group (4) National Publications or International publications (5) Publications in national and international journals (6) Can draft textbooks with ISBN.